2016
DOI: 10.1155/2016/2636390
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Prediction of Advanced Liver Fibrosis Using the Decision Tree Learning Algorithm in Chronic Hepatitis C Egyptian Patients

Abstract: Background/Aim. Respectively with the prevalence of chronic hepatitis C in the world, using noninvasive methods as an alternative method in staging chronic liver diseases for avoiding the drawbacks of biopsy is significantly increasing. The aim of this study is to combine the serum biomarkers and clinical information to develop a classification model that can predict advanced liver fibrosis. Methods. 39,567 patients with chronic hepatitis C were included and randomly divided into two separate sets. Liver fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…The severity of hepatic fibrosis was associated with elevated serum AFP level in accordance with other studies (17,18). PLT and serum albumin level were also found to be independent predictors of fibrosis (17,39), however, multivariate analysis in our study revealed only age and PLT as the independent predictors of advanced fibrosis.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The severity of hepatic fibrosis was associated with elevated serum AFP level in accordance with other studies (17,18). PLT and serum albumin level were also found to be independent predictors of fibrosis (17,39), however, multivariate analysis in our study revealed only age and PLT as the independent predictors of advanced fibrosis.…”
Section: Discussioncontrasting
confidence: 65%
“…An alternative way to build a decision tree is to grow a large tree, and then prune it by removing the nodes that provide less additional information. Pruning enhances tree comprehensibility while maintaining (or rather improving) its accuracy and should be performed in a bottom-up fashion (47,48 (39).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these data are stored in large sets on powerful computers owned by the companies we deal with every day that they understand our mind for purchase. The same goes for physicians and researchers who understand each disease behavior [24][25][26][27][28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…We further addressed the issue of performance evaluation of decision tree classifiers, where we assessed the correctly classified instances, recall, precession, and area under the curve [14]. Hashem, et al used the decision tree learning algorithm to provide an accurate prediction of advanced Liver fibrosis in CHC [15].…”
Section: Related Workmentioning
confidence: 99%